RECONCEPTUALIZING ENGLISH LANGUAGE TEACHING IN THE PHILIPPINES: INTERPLAY OF JOURNALING AND EMOTIONS - Villarama, Joseph A.; Dela Cruz, Lyan Mae Micah V.; Barcelita, Karen Jean C.; Jose, Baby Jean V. (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
While language teaching focuses on structural aspects, intricacies of any language come along with schema and emotion. Journaling, recognized as reflective-effective language teaching strategy, augmenting lifelong skills, remains underexplored in its interplay with language and emotions in second language teaching and learning. This phenomenological qualitative research determined the impact of journaling on ESL learners’ writing and emotional aspects. Responses of 61 Grade 8 ESL learners from provincial laboratory Science high school in Central Luzon, Philippines, during the Academic Year 2023-2024, were chosen through non-probability sampling method. After a series of in-depth face-to-face interviews guided by a set of 10 validated self-developed guide questions, responses were systematically arranged, coded, analyzed, characterized, and thematically interpreted. Findings reveal that through journaling, ESL learners showed engaging and positive language learning experience. While approaching journal writing tasks, the ESL learners involved a piece of themselves, transcending writing at a personal-academic level rather than structural-technical alone. As ESL learners improved language and emotional skills through journaling, they were still cognizant of being judged by peers and teachers. This research contributes to comprehensive understanding of reflective writing practices in language education, providing evidence-based insights for educators and policymakers to enhance both academic and emotional aspects of ESL learners’ experiences.